Physicians' electronic inbox work patterns and factors associated with high inbox work duration. (15th October 2020) - Akbar, Fatema; Mark, Gloria; Warton, E. Margaret; Reed, Mary E; Prausnitz, Stephanie; East, Jeffrey A; Moeller, Mark F; Lieu, Tracy A
Abstract: Objectives: Electronic health record systems are increasingly used to send messages to physicians, but research on physicians' inbox use patterns is limited. This study's aims were to (1) quantify the time primary care physicians (PCPs) spend managing inboxes; (2) describe daily patterns of inbox use; (3) investigate which types of messages consume the most time; and (4) identify factors associated with inbox work duration. Materials and Methods: We analyzed 1 month of electronic inbox data for 1275 PCPs in a large medical group and linked these data with physicians' demographic data. Results: PCPs spent an average of 52 minutes on inbox management on workdays, including 19 minutes (37%) outside work hours. Temporal patterns of electronic inbox use differed from other EHR functions such as charting. Patient-initiated messages (28%) and results (29%) accounted for the most inbox work time. PCPs with higher inbox work duration were more likely to be female ( P < .001), have more patient encounters ( P < .001), have older patients ( P < .001), spend proportionally more time on patient messages ( P < .001), and spend more time per message ( P < .001). Compared with PCPs with the lowest duration of time on inbox work, PCPs with the highest duration had more message views per workday (200 vs 109; P < .001) and spent more time on the inbox outside work hours (30 minutes vs 9.7 minutes; P < .001). Conclusions: Electronic inbox work by PCPs requires roughly an hour per workday, much of which occurs outside scheduled work hours. Interventions to assist PCPs in handling patient-initiated messages and results may help alleviate inbox workload.